Essential Role of Smooth Muscle STIM1 in Hypertension and Cardiovascular Dysfunction. Issue 9 (September 2016) - Kassan, Modar; Ait-Aissa, Karima; Radwan, Eman; Mali, Vishal; Haddox, Samuel; Gabani, Mohanad; Zhang, Wei; Belmadani, Souad; Irani, Kaikobad; Trebak, Mohamed; Matrougui, Khalid
Abstract : Objectives—: Chronic hypertension is the most critical risk factor for cardiovascular disease, heart failure, and stroke. Approach and Results—: Here we show that wild-type mice infused with angiotensin II develop hypertension, cardiac hypertrophy, perivascular fibrosis, and endothelial dysfunction with enhanced stromal interaction molecule 1 (STIM1) expression in heart and vessels. All these pathologies were significantly blunted in mice lacking STIM1 specifically in smooth muscle (Stim1 SMC−/− ). Mechanistically, STIM1 upregulation during angiotensin II–induced hypertension was associated with enhanced endoplasmic reticulum stress, and smooth muscle STIM1 was required for endoplasmic reticulum stress–induced vascular dysfunction through transforming growth factor-β and nicotinamide adenine dinucleotide phosphate oxidase–dependent pathways. Accordingly, knockout mice for the endoplasmic reticulum stress proapoptotic transcriptional factor, CCAAT-enhancer–binding protein homologous protein (CHOP −/− ), were resistant to hypertension-induced cardiovascular pathologies. Wild-type mice infused with angiotensin II, but not Stim1 SMC−/− or CHOP −/− mice showed elevated vascular nicotinamide adenine dinucleotide phosphate oxidase activity and reduced phosphorylated endothelial nitric oxide synthase, cGMP, and nitrite levels. Conclusions—: Thus, smooth muscle STIM1 plays a crucial role in the development of hypertension and associated cardiovascular pathologies and represents a promising target for cardiovascular therapy. Abstract : Supplemental Digital Content is available in the text.